Asuhan Kebidanan Komprehensif pada Ny. S Umur 25 Tahun dengan Kekurangan Energi Kronis (KEK) di Wilayah Puskesmas Bumiayu Kabupaten Brebes Tahun 2025 - Liana Anggraeni; Hafsah Hafsah; Riyanti Riyanti (PPNI UNIMMAN, 2026)
The highest mortality cases during pregnancy until the postpartum period are caused by several factors such as hypertension, infection, bleeding, anemia and KEK. Data obtained from pregnant women at the Bumiayu Community Health Center in 2023 were 30 cases, in 2024 there was an increase of 183 cases and in 2025 from January to February there were 30 KEK cases (Bumiayu Community Health Center profile, 2025). The purpose of the study was to provide comprehensive midwifery care to pregnant women, childbirth, newborns, postpartum and family planning (KB) using the Varney and SOAP management approaches. The method used in this study is a qualitative descriptive method with a comprehensive case study approach. The results of the study of comprehensive midwifery care to Mrs. S found problems in pregnancy with KEK have been given management according to the mother's needs. In labor, newborns, postpartum to KB Mrs. S there were no complications. Conclusion Comprehensive midwifery care to Mrs. S with KEK has been carried out in accordance with Standard Operating Procedures with the condition of the mother and baby being good.